INFLUENCE OF IMAGE VISUALIZATION AND AUDIOVISUAL TO INCREASED DIETARY ADHERENCE TOWARD DIABETES MELLITUS PATIENTS TYPE II IN HEALTH CENTER OF GORONTALO DISTRICT - Ani Retni (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
The purpose of research is to determine the influence of images visualization and audiovisual to increase dietary adherence in diabetes mellitus patients type II. The design of research is used quasi experimental with pretest-posttest form with control group design that used technique cluster sampling and 42 respondents were divided into 21 groups of control and intervention group 21 diabetes mellitus patients type II, and the data analysis is used Chi Square test. The result is there is no difference in improvement of dietary compliance before and after pictures and audiovisual educational visualization in the control group and the intervention group with p value = 0.039. Health Center Suggestions is expected to contain policies to develop educational methods diabetes mellitus, with the application of visualization of images and audiovisual media about diet and diabetes complications in improving compliance.